2021
DOI: 10.1111/pde.14807
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin‐induced visual hallucinations in a patient with acne vulgaris

Abstract: Oral isotretinoin is an effective treatment for severe acne. However, psychiatric side effects are noted, including a few cases of psychosis and mania triggered by isotretinoin. In this report, we present a case of visual hallucinations due to isotretinoin. In our case, with the discontinuation of isotretinoin, the hallucinations regressed and no other cause was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“… 36 Some investigators have reported the greatest reduction in both psychological and skin disease was achieved with oral isotretinoin therapy. 36 Isotretinoin has been linked to depression, suicide, psychosis and mania, 36 , 46 but a recent population-based study found no increased risk of psychiatric disorders associated with this drug. 47 As isotretinoin can reduce expression of MMPs, the reduction in depressive symptoms in acne patients may be explained in part through this anti-inflammatory effect.…”
Section: Resultsmentioning
confidence: 99%
“… 36 Some investigators have reported the greatest reduction in both psychological and skin disease was achieved with oral isotretinoin therapy. 36 Isotretinoin has been linked to depression, suicide, psychosis and mania, 36 , 46 but a recent population-based study found no increased risk of psychiatric disorders associated with this drug. 47 As isotretinoin can reduce expression of MMPs, the reduction in depressive symptoms in acne patients may be explained in part through this anti-inflammatory effect.…”
Section: Resultsmentioning
confidence: 99%